Some language policy in José Hernández (Anclajes, 2025)
An overview is offered of the conceptions of linguistic policy that were debated in Argentina, specifically in the River Plate area, during the second half of the 19th century. Following the sinuous lines drawn by Juan Bautista Alberdi and Domingo Faustino Sarmiento for or against the hegemony of the Castilian normative variety, the article focuses on the contributions of José Hernández, mainly in his political articles in El Río de la Plata (Buenos Aires, 1869-70) and in some scenes of Martín Fierro that fictionalize linguistic conflict.
Keywords: Language policy; Americanism; Río de la Plata; José Hernández; Argentina